Model of Country’s Geoeconomic Position Identification in Terms of International Integration - Kostenko, N.V. (Економічний вісник Донбасу, 2013)
Article gives technique of country’s geo-economic position identification adjusted for an integration vector. This technique is based on United Nations University research (RIKS, UNESCAP, Asian Development Bank). Nature of international integration was grounded according to “Beijing Consensus” doctrine, which replaced the “Washington Consensus” doctrine. “Beijing Consensus” is perceived as economic regionalization doctrine resulting in formation of interactive and competitive regional arrangements, which create foundation for modern multipolar management of the world economy. Author gave evidence in favour of positive effect that regional integration has on member-countries’ development. Logical model for identification of country’s geo-economic position at the conclusion of regional trade agreements (RTA) was developed in the article. Pre-analysis method (ex ante) was assumed as a basis for the model. Author also defined geo-economic position of Ukraine in regional integration with the CIS countries. Export indices of Ukrainian products at the CIS market were calculated on the basis of 86th commodity group.